Webster's New Geographical Dictionary (USA Merriam-Webster Inc., 1988)
More than 47,000 entries and 218 maps provide information on the world's continents, countries, regions, cities, and natural features.
Keywords: Languages (3GddZGJs; General; Gazetteers; Geography -- Dictionary -- English